Efficacy of sodium hypochlorite and chlorhexidine against Enterococcus faecalis: a systematic review - Estrela, Carlos; Silva, Julio Almeida; Alencar, Ana Helena Gonçalves de; Leles, Claudio Rodrigues; Decurcio, Daniel Almeida (Journal of Applied Oral Science, 2008)
The efficacy of the sodium hypochlorite (NaOCl) and chlorhexidine (CHX) on Enterococcus faecalis was evaluated by systematic review and meta-analysis. The search strategies included search in electronic biomedical journal databases (MEDLINE, EMBASE, CENTRAL) and handsearching records, using different matches of keywords for NaOCl, CHX and Enterococcus faecalis. From 41 in vivo studies, 5 studies met the inclusion criteria. In a sample containing 159 teeth, E. faecalis was detected initially in 16 (10%) teeth by polymerase chain reaction (PCR) and 42 (26.4%) teeth by microbial culture techniques. After root canal disinfection, this species was observed in 11 (6.9%) teeth by PCR and 12 (7.5%) teeth by culture. Risk differences of included studies were combined as generic inverse variance data type (Review Manager Version 5.0 _ Cochrane Collaboration, http://www.cc-ims.net, accessed 15 May 2008), taking into account the separate tracking of positive and negative cultures/PCR. The level of statistical significance was set at p